Sejarah dan Konsep Dasar Psikologi Belajar dalam Pendidikan Agama Islam - Putri, Yuliana; Yoma, Abdul Razzak; Fitriani, Wahidah (Lembaga Yasin AlSys, 2025)
The study of the history and foundational concepts of learning psychology within the context of Islamic Religious Education (Pendidikan Agama Islam, PAI) is essential for understanding the theoretical basis of instructional strategies rooted in Islamic values. This research aims to trace the evolution of learning psychology and to elucidate its core concepts relevant to Islamic education. The study employs a library research method with a qualitative descriptive approach by analyzing classical and contemporary literature on learning psychology and its connection to PAI. The analysis reveals that the development of learning psychology originates from classical philosophy, Islamic thought in the medieval period, and extends to modern theories encompassing behaviorist, cognitive, social, and humanistic approaches. In the context of PAI, fundamental concepts of learning psychology include relatively permanent behavioral changes, cognitive processes, intrinsic and extrinsic motivation, and the influence of social experience. The Islamic perspective enriches these approaches with a spiritual dimension aimed at nurturing knowledgeable, faithful, and morally upright individuals in accordance with the teachings of the Qur’an and Sunnah. These findings highlight the importance of integrating the principles of learning psychology with Islamic values in the development of curriculum, learning strategies, and future research directions in PAI.